Investigation of optimal lower body movement in presence of the constrained pelvis rotation in baseball batting - Ae, K.; Burke, D.; Kawamura, T.; Koike, S. (Journal of Biomechanics, 2022)
Baseball batting is a skilful whole-body motion and hitting a ball properly requires both accurate spatial and temporal coordination; thus it is one of the most difficult skills in sport (DeRenne et al., 2008, Race, 1961). If the coordination of the bat-ball impact is maintained, improved batting performance, i.e., higher velocity of the batted ball, will result from higher bat-head speed at impact (Sawicki et al., 2003). Batters generate bat-head speed using a kinetic chain that transfers mechanical energy from the lower body to upper limbs and bat (Ae et al., 2017, Horiuchi et al., 2021, Welch et al., 1995). Therefore exploring the lower limb movements responsible for the generation of mechanical energy and bat-head speed can provide insight into how to improve batting performance.